Challenges of Mapping the Classical World - Talbert, Richard J. A. (Routledge, 2018)
Cover -- Title -- Copyright -- Dedication -- Contents -- Preface and Acknowledgements -- Introduction -- 1 Walter Goffart's Historical Atlases: The First Three Hundred Years, 1570-1870 (Chicago and London: The University of Chicago Press, 2003). Review in History Today December 2003, p. 58 -- 2 William Smith and George Grove, eds., Atlas of Ancient Geography Biblical and Classical (1872-1874): Introduction to the 2013 Reissue (London: I. B. Tauris, 2013, pp. v-xii) -- 3 Carl Müller (1813-1894), S. Jacobs, and the Making of Classical Maps in Paris for John Murray ( Imago Mundi 46: 1994. pp. 128-50) -- 4 A Forgotten Masterpiece of Cartography for Roman Historians: Pierre Lapie's Orbis Romanus ad Illustranda Itineraria (1845) in H. M. Schellenberg, V. E. Hirschmann, Andreas Krieckhaus, eds., A Roman Miscellany: Essays in Honour of Anthony R. Birley on -- 5 Heinrich Kiepert, Formae Orbis Antiqui (1894-1914) : Introduction to the 1996 Reissue (Rome: Edizioni Quasar, 1996, pp. V-VIII) -- 6 The Primary Classical Atlases and Map Series between 1870 and 1990 (1992) -- 7 Ségolène Débarre's Cartographier l'Asie Mineure: L'orientalisme allemand à l'épreuve du terrain (1835-1895) (Paris: Peeters, 2016). Review in Bryn Mawr Classical Review 2017.05.27 -- 8 Classical Atlas Project: Narrative Description 1990 (unpublished) -- 9 Classical Atlas Project: Instructions for Compilers 1990 (unpublished) -- 10 Classical Atlas Project: Half-yearly Reports to the U.S. National Endowment for the Humanities, August 1991-May 2000 (unpublished) -- 11 Maps for the Classical World: Where Do We Go from Here? (American Journal of Philology 118.2: 1997. pp. 323-27) -- 12 Barrington Atlas of the Greek and Roman World : The Cartographic Fundamentals in Retrospect ( Cartographic Perspectives 46: 2003. pp. 4-27 and 72-76).